SAUDI ARABIAN WOMAN’S MARRIAGE LIFE IN GIRLS OF RIYADH, A NOVEL BY RAJAA ALSANEA: SUBORDINATION AND STRUGGLE - THALIB, AMIRAH ANIS (Jurnal Ilmiah Mahasiswa FIB, 2013)
This article argues that implementation of Pre-Islamic tradition and culture emerges subordination toward woman in Saudi Arabia. They face subordination in many aspects of life. This phenomenon can be found in Girls of Riyadh novel. In this novel, Rajaa Alsanea, a Saudi Arabian woman writer tells how women live under male domination. In analyzing the phenomena, the writer used feminist approach by applying feminism theory which is combined with Islamic references to reveal subordination and struggle of woman depicted in the novel. It will focus on subordination of woman and her struggle in marriage matters rather than on other aspects. Keywords: Subordination, Struggle, Woman, Saudi Arabia, Feminism.